Degree of dopaminergic degeneration measured by 99mTc-TRODAT-1 SPECT/CT imaging - Ling Lin; Jing Ye; Han Zhang; Zhong-Fu Han; Zhi-Hong Zheng (Neural Regeneration Research, 2018)
To prevent and treat Parkinson’s disease in its early stages, it is essential to be able to detect the degree of early dopaminergic neuron degeneration. Dopamine transporters (DAT) in the striatum regulate synaptic dopamine levels, and striatal 99mTc-TRODAT-1 single-photon emission computed tomography (-SPECT) imaging is a marker for presynaptic neuronal degeneration. However, the association between the degree of dopaminergic degeneration and in vivo 99mTc-TRODAT-1 SPECT imaging is unknown. Therefore, this study investigated the association between the degree of 6-hydroxydopamine (6-OHDA)-induced dopaminergic degeneration and DAT imaging using 99mTc-TRODAT-1 SPECT in rats. Different degrees of nigrostriatal dopamine depletion were generated by injecting different doses of 6-OHDA (2, 4, and 8 μg) into the right medial forebrain bundle. The degree of nigrostriatal dopaminergic neuron degeneration was assessed by rotational behavior and immunohistochemical staining. The results showed that striatal 99mTc-TRODAT-1 binding was significantly diminished both in the ipsilateral and the contralateral sides in the 4 and 8 μg 6-OHDA groups, and that DAT 99mTc-TRODAT-1 binding in the ipsilateral striatum showed a high correlation to apomorphine-induced rotations at 8 weeks post-lesion (r = –0.887, P < 0.01). There were significant correlations between DAT 99mTc-TRODAT-1 binding in the ipsilateral striatum and the amount of tyrosine hydroxylase immunoreactive neurons in the ipsilateral substantia nigra in the 2, 4, and 8 μg 6-OHDA groups at 8 weeks post-lesion (r = 0.899, P < 0.01). These findings indicate that striatal DAT imaging using 99mTc-TRODAT-1 is a useful technique for evaluating the severity of dopaminergic degeneration.